The Effect of Using Wattpad Application to Improving Student’s Reading Comprehension of Recount Text at Tenth Grade Students of Senior High School Number 11 Jambi - Mawarni, Sania; Ismiyati, Yanti; Dinata, Ridho Praja (JELT: Journal of English Language Teaching, 2023)
Many students are more captivated by reading through the internet and application media than reading a book, one example of reading application the Wattpad application, this application is an electronic book in the form of an application, on Wattpad there are many things that can be read in the Wattpad application. This study employed a true experiment design, using quantitatively approved pre-test and post-test. Genuine experiment with pre- and post-tests This study's type of research design is group design. Or in Indonesian known as true experiment, is the most rigorous and powerful experimental design because in true experiment research the research subject is randomly selected. Before providing treatment, the exam should determine the kids'' reading comprehension. In the pre-test experimental group, the researcher obtained 36 sample scores with means of 55, 35, 63, and 40. In the post-test score following treatment, the researcher obtained 36 sample scores with means of 75, 35, 90, and 35. Based on the theory of reading using the Wattpad application it can help students to improve their reading skill and students can read understand a content of the story text.